2022
DOI: 10.1039/d1ra09446g
|View full text |Cite
|
Sign up to set email alerts
|

Tuning luminescence of the fluorescent molecule 2-(2-hydroxyphenyl)-1H-benzimidazole via zeolitic imidazolate framework-8

Abstract: ZIF-8 is regarded as a carrier to capture HPBI and eventually the adsorption of the pore structure would saturate, with altering the luminescent intensity. ZIF-8 may be used to sensitively detect nanoscale molecules via changes in fluorescence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…The role that ZIF-8 played in tuning HPBI molecular fluorescence has already been studied in our previous work, [40] and in the present work the fluorescence results of ZIF-8 mixed with HPBI molecules were mainly used as a comparison with AuNPs@ZIF-8. In our previous work, [40] we had already investigated that when ZIF-8 was added to the HPBI solution, the PL intensity of the mixture increased as the blending time increased from 5 min to 120 min. From 120 min to 240 min, the increment slowed down, and by the end of 16 h, the PL intensity had no obvious enhancement.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…The role that ZIF-8 played in tuning HPBI molecular fluorescence has already been studied in our previous work, [40] and in the present work the fluorescence results of ZIF-8 mixed with HPBI molecules were mainly used as a comparison with AuNPs@ZIF-8. In our previous work, [40] we had already investigated that when ZIF-8 was added to the HPBI solution, the PL intensity of the mixture increased as the blending time increased from 5 min to 120 min. From 120 min to 240 min, the increment slowed down, and by the end of 16 h, the PL intensity had no obvious enhancement.…”
Section: Resultsmentioning
confidence: 93%
“…The mixture was also accompanied by a blue shift, which can be attributed to Zn 2+ . [40] All results indicate that the pores of ZIF-8 can limit the vibration and rotation of the molecules, resulting in increased emission efficiency, [44] and that there is a π-π stacking between the benzene ring of HPBI and the imidazole ring in the ZIF-8 structure. [45,46] We have already obtained the effects of ZIF-8 crystals and AuNPs on the fluorescence properties of HPBI molecules.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The high porosity and regular channels of MOFs make them a kind of ideal host materials. The properties of the guest fluorescent molecules may be changed after being integrated into MOFs. Recently, we also found that zeolitic imidazolate framework-8 (ZIF-8) nanoparticles could tune the luminescence of a specific fluorescent molecule 2-(2-hydroxyphenyl)-1 H -benzimidazole (HPBI) and achieve significant fluorescence enhancement . However, unlike metallic particles, which have been found to employ the plasmonic resonance to achieve fluorescence enhancement, it is still unclear how MOF particles accommodate the fluorescent molecules and therefore exhibit enhanced fluorescence.…”
Section: Introductionmentioning
confidence: 99%
“…At present, two fundamental issues need to be addressed before MOF films can be used as electrolytes in fuel cells, namely how to easily prepare stable films and how to obtain high proton conductivity. The dense thin films are very important to the proton exchange mechanism in fuel cells [16]; the means of preparing dense and electrical conductivity-controlled thin films are studied in this paper [17,18]. MOF-508a (Zn(BDC)(4,4 -bipy) 0.5 DMF(H 2 O) 0.5 with a 3D structure containing a 1D channel (valid pore diameter of 4 × 4 Å) was selected [19]; from this we prepared dense, micron-sized thin films on a Zn substrate via the "twin-zinc-source" method [20,21].…”
Section: Introductionmentioning
confidence: 99%